Perancangan Corporate Identity Rumah Sakit Umum Daerah Bukittinggi - Hanif, Raihan; Sudiani, Yoni; Malik, kendall; khairunnisa, Khairunnisa (SPACEPRO: Product Design Jurnal, 2024)
In the management of hospitals, Corporate Identity plays a pivotal role in brand recognition, image formation, and public perception. The primary objective behind the establishment of the hospital's Corporate Identity is to facilitate the audience's ability to remember and trust the institution as a professional and highly competent healthcare service provider, thereby fostering loyalty among the target audience.The main challenge faced by RSUD Bukittinggi is the absence of a clear corporate identity, serving as a reminder to the community and patients regarding the positive image and unique characteristics of RSUD Bukittinggi. Furthermore, this corporate identity also serves as a distinguishing factor for RSUD Bukittinggi from other healthcare facilities.In light of this, RSUD Bukittinggi requires innovative ideas in constructing a Corporate Identity that can effectively present the image, unique characteristics, and excellence possessed by RSUD Bukittinggi. The existence of RSUD Bukittinggi as a hospital offering medical tourism services in the city of Bukittinggi demands a corporate identity befitting its distinguished position.As a comprehensive solution to address this issue, a step taken is to design a corporate identity strategy for RSUD Bukittinggi utilizing the SWOT analysis method. This strategic approach can yield results that are congruent and highly effective in conveying the identity and distinctive characteristics of this institution. Components of this comprehensive corporate identity strategy include logo creation, typography selection, determination of identity colors, and utilization of various communication channels, all meticulously designed to facilitate the audience in identifying the unique characteristics and excellence of RSUD Bukittinggi.Keywords: Corporate identity, RSUD Bukittinggi